2020
DOI: 10.3390/molecules25071737
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effect of Arctium Lappa L. Leaves on Retinal Damage Against A2E-Induced ARPE-19 Cells and Mice

Abstract: Age-related macular degeneration (AMD) is a major cause of irreversible loss of vision with 80–90% of patients demonstrating dry type AMD. Dry AMD could possibly be prevented by polyphenol-rich medicinal foods by the inhibition of N-retinylidene-N-retinylethanolamine (A2E)-induced oxidative stress and cell damage. Arctium lappa L. (AL) leaves are medicinal and have antioxidant activity. The purpose of this study was to elucidate the protective effects of the extract of AL leaves (ALE) on dry AMD models, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 57 publications
0
14
0
1
Order By: Relevance
“…Based on the apoptotic pathway, the candidates can be grouped into (1) anti-oxidative stress, (2) anti-inflammation, and (3) anti-carbonyl stress candidates. One hundred percent EtOH extract of Arctium lappa L. leaves has been found to have plentiful amounts of phenolics and flavonoids, and it effectively suppressed both oxidative stress by scavenging effects of 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)(ABTS) and apoptosis by modulating bcl-2 family and caspase cascade [ 104 ]. Genipin is a glycosidic ligand that has been found to suppress H 2 O 2 -induced oxidative stress and apoptosis via nuclear factor-erythroid 2-related factor-2 (Nrf2), which regulates the expression of heme oxygenase-1 (HO-1) and NAD(P)H: quinine oxidoreductase 1 (NQOA) [ 105 ].…”
Section: Drug Candidates Originated From Natural Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the apoptotic pathway, the candidates can be grouped into (1) anti-oxidative stress, (2) anti-inflammation, and (3) anti-carbonyl stress candidates. One hundred percent EtOH extract of Arctium lappa L. leaves has been found to have plentiful amounts of phenolics and flavonoids, and it effectively suppressed both oxidative stress by scavenging effects of 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)(ABTS) and apoptosis by modulating bcl-2 family and caspase cascade [ 104 ]. Genipin is a glycosidic ligand that has been found to suppress H 2 O 2 -induced oxidative stress and apoptosis via nuclear factor-erythroid 2-related factor-2 (Nrf2), which regulates the expression of heme oxygenase-1 (HO-1) and NAD(P)H: quinine oxidoreductase 1 (NQOA) [ 105 ].…”
Section: Drug Candidates Originated From Natural Productsmentioning
confidence: 99%
“…From this reason, many natural products that can possibly constrain AMD severity have been used and investigated. Based on their modes of action, they can be divided into those that are preventers of RPE death/cell cycle arrest (anti-apoptosis inducers and cell cycle arrest modulators) [ 104 , 105 , 107 , 108 , 109 , 110 , 111 , 112 ] and those that are inhibitors of VEGF activation (VEGF inactivators) [ 38 ]. Natural products are safer than synthetic chemicals, as they have been used for a long time, they have an easy route of administration, with most able to be orally applied, and they can be used as combined therapies, such as with device-based therapy, anti-inflammatory drugs, and anti-VEGF molecules.…”
Section: Perspectivesmentioning
confidence: 99%
“…[7] Modern research implied that burdock leaves can have anti-microbial, anti-cancer, anti-inflammatory, anti-oxidant effects, and retinal protective effects. [7,12,13] The theory of "toxin damaging brain collaterals" is a major pathogenesis of AD in TCM. [14] Heat-clearing and toxicityremoving therapy, such as Huang-Lian-Jie-Du Decoction, was widely used to ameliorate AD.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] Modern research implied that burdock leaves can have anti‐microbial, anti‐cancer, anti‐inflammatory, anti‐oxidant effects, and retinal protective effects. [ 7,12,13 ]…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they suggested that compounds such as chlorogenic acid, o-hydroxybenzoic acid, caffeic acid, p -coumaric acid and rutin present in A. lappa leaves extracts could be involved in antioxidant activity. More recently, Kim et al [ 28 ] showed that an A. lappa leaves extract has a protective effect on an age-related macular degeneration model and they suggested that this effect could be due to antioxidant properties of phenolic and flavonoid content present in the leaves extract. Thus, all these studies have reported a potential antioxidant ability of A. lappa leaves but no specific compound has been isolated from the extracts.…”
Section: Introductionmentioning
confidence: 99%